2015
DOI: 10.1088/0957-4484/26/46/465302
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring graphene by dense electronic excitation

Abstract: The ability to manufacture tailored graphene nanostructures is a key factor to fully exploit its enormous technological potential. We have investigated nanostructures created in graphene by swift heavy ion induced folding. For our experiments, single layers of graphene exfoliated on various substrates and freestanding graphene have been irradiated and analyzed by atomic force and high resolution transmission electron microscopy as well as Raman spectroscopy. We show that the dense electronic excitation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…Only a few experimental studies have addressed the effect of SHI irradiation in graphene [26,27,28,29,30,31,32,33]. Most of these experiments were performed on supported graphene and under oblique incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few experimental studies have addressed the effect of SHI irradiation in graphene [26,27,28,29,30,31,32,33]. Most of these experiments were performed on supported graphene and under oblique incidence.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by either highly charged or by very fast (swift) heavy ions. For both it has been shown that they can be used for defect engineering of 2D materials such as carbon nano-membranes, 26,27 graphene, [28][29][30][31][32][33] hexagonal boron nitride, 34 and MoS 2 . [35][36][37] Swift heavy ions (SHI) excite target atoms along their trajectory and the corresponding energy deposited per track length into the target material is usually given in terms of electronic stopping power S e = dE/dx.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of the velocity effect, medium sized accelerators can provide important complementary data at energies below 1 MeV amu −1 which are not easily accessible to large accelerators. In particular, the threshold for ion track formation constitutes an important experimental quantity (often needed for testing various ion-solid interaction models) that can be in many cases easily accessible to medium sized accelerators [1,9,11,16,19,25,26]. Similar to ion tracks in the bulk, there is always a threshold for nanohillock formation on the surface.…”
Section: Introductionmentioning
confidence: 99%